PERSEPSI GURU TENTANG STRES KERJA, COUNTERPRODUCTIVE WORK BEHAVIOR (CWB), DAN NEGATIVE AFFECTIVITY (Studi Pada Guru Sekolah Menengah Pertama Di Banda Aceh) - Vilzati Vilzati; Lita Ajirna; Mahdani Ibrahim (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2016)
This study aims to analyze the phenomenon of teacher work stress behavior at SMPN in Banda Aceh City which has impact on counterproductive work behavior (CWB). Where the negative affectivity as a control variable to the relationship between the two behaviors. Sample of 103 people taken based on random sampling technique. Primary data collection is done by distributing questionnaires to specified sample members. Data analysis using Moderate Regression Analysis (MRA), with the help of SPSS (Statistic Package for Social Science) devices. The analysis of the results of this study found that teacher work stress had negative impact on CWB, with coefficient value (β) of -0.390. Furthermore, Negative Affectivity has negative impact on CWB behavior, with coefficient value (β) of -0.301, and negative affectivity moderate the impact of work stress relation on CWB behavior, at the teacher of SMP Negeri in Banda Aceh City, with regression coefficient (β) 0,653. This result means that Negative Affectivity has a strong relationship in influencing job stress and CWB behavior on the teacher.